Earth's changing surface (Boston, MA., 2005)
This book consists of the following four chapter: mapping earth's surface, weathering and soil formation, erosion and deposition, and trip through geologic time.
Keywords: Science,Scientific recreations,Science museums; Experiments,Educational aspects; Juvenile literature